Comparative historical dialectology : Italo-Romance clues to Ibero-Romance sound change - Cravens, Thomas D. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2002)
This brief monograph explores the historical motivations for two sets of phonological changes in some varieties of Romance: restructured voicing of intervocalic /p t k/, and palatalization of initial /l/ and /n/. These developments have been treated repeatedly over the decades, yet neither has enjoyed a satisfactory solution. This book attempts to demonstrate that both outcomes are ultimately attributable to the loss of early pan-Romance consonant gemination. This study is of interest not only to the language-specific field of historical Romance linguistics, but also to general historical lingu.